Oncology in midlife and beyond. (October 2013) - Gompel, A.; Baber, R. J.; de Villiers, T. J.; Huang, K.-E.; Santen, R. J.; Shah, D.; Villaseca, P.; Shapiro, S.
Abstract The onset of the menopause is often a time when women's concerns can act as a powerful trigger to encourage healthy modifications in lifestyle which will maintain, or improve, their general health. This document aims to help women to understand their potential risks, to encourage them to find proactive preventive strategies by modifying some of their attitudes, and to use health resources (when available) to be screened. Cancer is an important cause of death but not the primary cause of mortality. Cardio/circulatory diseases represent 35–40% of causes of death in most developed countries and 20–25% of women will die from cancers in Western Europe, Australasia, high-income North America, high-income Asia Pacific, East Asia and Southern Latin America. Breast cancer, lung cancer and colorectal cancer are prevalent in most regions of the world. Cervical cancer remains a hallmark of low access to health care. Preventive strategies (decreasing smoking and alcohol consumption, losing weight, eating a healthy diet and undertaking physical activity) and implementation of screening could help to significantly decrease the incidence of and mortality from cancer. The mortality/incidence ratio is higher in developing countries compared to high-income regions as well as in subgroups of populations in developed countries with lower socioeconomic levels. Implementation of better diagnostic methods and management of cancer according to the local resources will help to decrease the mortality rate in developing countries, and effort has to be made to decrease social inequities and improve access to health care for low-income groups. In conclusion, cancer incidence is increasing as a consequence of longer life expectancy all over the world. National health programs are mandatory to implement screening and to improve individual management. Finally, educating women so that they are aware of ways to improve their general health, to minimize their own risk factors and to identify signs of change in their own health which may be markers of impending cancer will help to reduce the burden of disease and improve the prognosis for tumors detected at an earlier stage.